Knowledge in transition in an industrial company - Sousa, M. J.; Sousa, M.; Rocha, Á. (Trends and Applications in Information Systems and Technologies. Advances in Intelligent Systems and Computing, 2021)
This research examines knowledge transition in an industrial company. This study presents findings about methods and forms of interaction and knowledge transition between organizational actors in innovation processes. Methodology is qualitative and quantitative, as the data was collected through interviews and questionnaires techniques. This study contributes to the body of knowledge about knowledge transition in innovation processes, and empirically presents the impacts of knowledge transition in several dimensions of the organization activity. Finally, the study provides directions for avenues of future research, and suggests some research questions arising out of these findings that might be explored.